DEVELOPMENT OF NANOPARTICLE FORMULATIONS LOADED WITH PHYTOCHEMICALS LIKE BERBERINE FOR ENHANCED ANTICANCER ACTIVITY - Pankaj Mohan Pimpalshende; Sujith S Nair; Shama Afroze Baig; Suganthi P; Shiwali Bisht; Umadevi A; Rangu Nirmala; Ashish Bhanudas Wadekar (The Bioscan, 2026)
The natural isoquinoline alkaloid Berberine (Brb) has strong multi-pathway anticancer activity which is severely limited by low aqueous solubility, rapid metabolism, and poor oral bioavailability. Purpose: The research paper assesses the design and effectiveness of several nanotechnology-based delivery systems that can be used to address these pharmacokinetic barriers.